2022
DOI: 10.1002/pits.22658
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' experiences with K‐12 students' mental health

Abstract: The purpose of this study was to explore teachers' experiences of student mental health concerns (SMHC) in the classroom. In this consensual qualitative research (CQR) study, we explored 12 teachers' experiences related to their SMHCs in the classroom. Five domains emerged from this CQR study: (1) Teachers' Responses to Student Mental Health Concerns, (2) Teachers' Perceptions of Preparedness in Addressing Student Mental Health, (3) Teacher Identified Preparation Needs to Addressing Student Mental Health, (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For instance, studies have indicated a positive dose-response relationship between training volume and mental health for female students, emphasizing the need for tailored interventions to address gender-specific mental health challenges (Grasdalsmoen et al, 2022). Furthermore, the results are consistent with the literature on educators' roles in supporting students' mental health, highlighting the importance of training and strategies to address mental health issues among students, particularly female students (Deaton et al, 2022;Soo, 2023).…”
Section: Discussionsupporting
confidence: 73%
“…For instance, studies have indicated a positive dose-response relationship between training volume and mental health for female students, emphasizing the need for tailored interventions to address gender-specific mental health challenges (Grasdalsmoen et al, 2022). Furthermore, the results are consistent with the literature on educators' roles in supporting students' mental health, highlighting the importance of training and strategies to address mental health issues among students, particularly female students (Deaton et al, 2022;Soo, 2023).…”
Section: Discussionsupporting
confidence: 73%
“…Once again, an interesting question arises: do support teachers and general teachers, who indicated that they had less experience, lack knowledge on how to help children because they don't understand the struggles caused by conditions such as depression, eating disorders, sleep disorders, or personality disorders, or do they have insufficient knowledge about the most common symptoms? Deaton et al (2022) indicated that teachers face a shortage of training and support in dealing with students with mental health challenges in the classroom, leading to numerous instances of trial and error. The subsequent analysis aimed to identify variations in teachers' emotional intelligence (EI) and social competences, recognized as crucial in the teaching profession (Ergur, 2009;Jennings & Greenberg, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…While research shows that training in mental health increases teachers’ confidence and knowledge of health issues [ 43 , 44 ], the inadequacies in training continue to be voiced by teachers. Teachers continue to ask for training that tells them: “here is what to do, or here is what to say” when a child or adolescent is experiencing a mental health issue [ 45 ]. Research suggests that studies need to address whether and how the perceived gap in teacher training is being addressed [ 41 ].…”
Section: Introductionmentioning
confidence: 99%